Analysis of N6-methyladenosine-modified mRNAs in diabetic cataract - Cai, Lei; Han, Xiao-Yan; Li, Dan; Ma, Dong-Mei; Shi, Yu-Meng; Lu, Yi; Yang, Jin (World journal of diabetes, 2023)
The prevalence of diabetes mellitus is increasing in resource limited settings. Simultaneously, there has been an increase in the number of novel therapies for the management of diabetes mellitus. However, use of novel antidiabetic therapies is limited because of major market access challenges in resource limited settings. Niching products to those patients with the highest absolute risk for major adverse cardiovascular outcomes, and thus most likely to benefit from the therapy, are less likely to have negative budget impact for funders. To improve access, and reduce morbidity and mortality, requires alignment amongst key stakeholders including patient advocacy groups, health care professional councils, national departments of health, the pharmaceutical industry, treasury and finance departments.